08.03 Il-17 and tnf-α induce in synergy an inflammatory response in hepatocytes through il-6-dependent and –independent pathways. (1st March 2017) - Beringer, Audrey; Thiam, Ndieme; Molle, Jennifer; Bartosch, Birke; Miossec, Pierre
Abstract : Background: The pro-inflammatory cytokines interleukin-6 (IL-6), interleukin-17A (IL-17A) and tumour necrosis factor-alpha (TNF-α) are involved in many autoimmune and inflammatory diseases including rheumatoid arthritis (RA). Many markers produced in response to inflammation by the liver, such are CRP, are associated with an increased risk of cardiovascular disease (CVD). We examined the IL-17A/TNF-α effect in the hepatic inflammatory response, compared to that of IL-6, on HepaRG hepatoma cell line and primary human hepatocytes (PHH). Materials and methods: HepaRG cells and PHH were cultured with or without IL-6, IL-17A and/or TNF-α. mRNA expression of IL-8, MCP-1 and CCL-20 chemokines and CRP and IL-6 was analysed by qRT-PCR. IL-6 and IL-8 production was measured by ELISA and the aspartate aminotransferase (ASAT) secretion by an automated analyzer. Anti-IL-6 receptor antibody or MAPK inhibitors were added to determine the possible contribution of IL-6 and the signalling pathway mediated by the IL-17A/TNF combination. Results: IL-17A and TNF-α induced in synergy hepatic IL-6 and IL-8 production (>8 fold, p<0.01). The expression of IL-6, IL-8, MCP-1, CCL-20 and CRP genes was also synergistically up-regulated (47-; 19-; 10-, 70- and 35-fold respectively, p<0.01) by the IL-17A/TNF-α combination in HepaRG cells. IL-8 up-regulation leads to neutrophil recruitment, involved in the acute-phase of inflammation. Furthermore MCP-1 and CCL-20 up-regulation leads to T cell, monocyte and dendritic cell recruitment involved in the chronicity of inflammatory response. The addition of an anti-IL-6 receptor antibody with the IL-17A/TNF-α exposure highly reduced the CRP expression (92% of inhibition, p<0.01) and the ASAT secretion (28% of inhibition, ASAT level similar to control) compared to the IL-17A/TNF-α-stimulated condition. By contrast, IL-8, MCP-1 and CCL-20 up-regulation after IL-17A/TNF-α-stimulation was not affected by IL-6 inhibition. The IL-17A/TNF-α synergistic effect was mediated through the ERK-MAPK-signalling pathway. Conclusions: IL-17A and TNF-α, acting in synergy, mediate systemic inflammation, by inducing CRP and possibly increasing CVD risk, and liver damage in hepatocytes through the IL-6 pathway. Conversely, the IL-17A/TNF-α combination synergistically increases IL-8, MCP-1 and CCL-20 expression independently of IL-6, leading to the recruitment of immune cells for the initiation and the chronicity of the inflammatory response.